(untitled) (Research, Society and Development, 2018)
This article discusses the 30 years of experience of direct elections for director of the Natal’s municipal education system. Aiming to reconstruct the history of this phenomenon since the first election that occurred in 1987. To this end, two other phenomena are added in the course of 30 years of experience: the organization of the first elections for the gave in collective instances of decision; and the institution of Law 147/2015 that established in the municipal public school network, the school management shared by two principals: one administrative-financial and one pedagogical. We assume as method for this research Historical and Dialectical Materialism; and as instruments, we use the conversational free interview and the documentary analysis. We conclude that pioneering and innovation in democratic management are presented as phenomena that allow the Natal’s teaching network to experience itself democratically, although there is still much to be done in democratic practices with a view to participatory democratic management.